2012
DOI: 10.4103/0971-6866.96667
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MLPA in mutation analysis and carrier detection for Duchenne muscular dystrophy

Abstract: CONTEXT:Multiplex ligation probe amplification (MLPA) is a new technique to identify deletions and duplications and can evaluate all 79 exons in dystrophin gene in patients with Duchenne muscular dystrophy (DMD). Being semi-quantitative, MLPA is also effective in detecting duplications and carrier testing of females; both of which cannot be done using multiplex PCR. It has found applications in diagnostics of many genetic disorders.AIM:To study the utility of MLPA in diagnosis and carrier detection for DMD.MAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In our study as represented in Table 2 and Supplementary Table 01, mPCR could provide molecular diagnosis for 55% (131/236) of the patients, of which 76% (100/136) of the patients the exact deletion boundaries accurately detected by mPCR. In line with our findings, studies conducted in South India [ 25 ] and North India [ 26 ] identified (103/150) 68% and (161/217) 74%, respectively, as the mutation detection Percentage by mPCR. Intriguingly in our study 95% (131/138) of the patients with deletion mutations could be diagnosed by mPCR.…”
Section: Discussionsupporting
confidence: 92%
“…In our study as represented in Table 2 and Supplementary Table 01, mPCR could provide molecular diagnosis for 55% (131/236) of the patients, of which 76% (100/136) of the patients the exact deletion boundaries accurately detected by mPCR. In line with our findings, studies conducted in South India [ 25 ] and North India [ 26 ] identified (103/150) 68% and (161/217) 74%, respectively, as the mutation detection Percentage by mPCR. Intriguingly in our study 95% (131/138) of the patients with deletion mutations could be diagnosed by mPCR.…”
Section: Discussionsupporting
confidence: 92%
“…46 MLPA has been used to detect carrier status in probands with known deletion or duplication mutations since it is an easy and quick technique. 47 Detection of carrier status serves to provide essential information for family counselling regarding future pregnancies, improving quality of life and reducing financial burden for at-risk families. 48 This study also shows that MLPA analysis can pave the way for future therapeutics in DMD patients by identifying amenable genotypes that can be targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, MLPA is an available method which can be used for prenatal diagnosis when the deletions or duplications are not detected by multiplex PCR. [ 23 ] Certainly, sequencing can be used to detect small gene mutations in MLPA-negative individuals. It is essential to perform antenatal diagnosis on the carriers of childbearing age by MLPA primarily.…”
Section: Discussionmentioning
confidence: 99%